Pelatihan Batik Jumputan untuk Meningkatkan Prestasi Non Akademik Siswa Kelas V Sekolah - Ratno Susanto; Achmad Afandi; Khusnul Khotimah (Lembaga Pengembangan Kinerja Dosen, 2025)
The school's fifth-grade kids receive jumputan batik instruction with the goal of enhancing both their creative abilities and extracurricular accomplishments. One batik-making technique that makes use of the tie-dye procedure is jumputan batik. Jumputan batik is made by tying thread in specific areas of the material and then dipping it in dye to create a unique design. In order to ensure that activities may be carried out efficiently and have the greatest possible influence on students' development, the process of carrying out this community service is structured from planning to evaluation. As a result, kids are able to freely and creatively express themselves through art-related activities. Students can make their own designs and patterns when making jumputan batik, which promotes original and creative thinking. The ability to create original designs is made possible by the jumputan batik process, which incorporates tie-dye elements. Pupils can use their imagination to create motifs, patterns, and color combinations that represent their own personalities and concepts. Students' critical and creative thinking abilities are greatly enhanced by this creative process. According to the findings, students now possess much greater creativity, self-confidence, discipline, and teamwork. In addition to teaching pupils traditional batik techniques, this instruction aids in the development of social and character traits that will benefit them greatly throughout their life. It is anticipated that by exposing more students to Indonesian art and culture, this instruction would be expanded and perpetuated. It is anticipated that by exposing more students to Indonesian art and culture, this instruction would be expanded and perpetuated.